Komposisi Karawitan “Maha Aksa” - I Made Andika Candra Wigraha; Ni Ketut Dewi Yulianti; I Nyoman Mariyana (Institut Seni Indonesia Denpasar, 2023)
Purpose: this karawitan artwork is to transform the idea obtained from the fly’s vision system into